Lung microwave ablation – an in vivo swine tumor model experiment to evaluate ablation zones. (1st January 2020) - Prud'homme, Clara; Teriitehau, Christophe; Adam, Julien; Kyaw Tun, Jimmy; Roux, Charles; Hakime, Antoine; Delpla, Alexandre; Deschamps, Fréderic; de Baere, Thierry; Tselikas, Lambros
Abstract: Purpose: To evaluate microwave ablation (MWA) algorithms, comparing pulsed and continuous mode in an in vivo lung tumor mimic model Materials and methods: A total of 43 lung tumor-mimic models of 1, 2 or 3 cm were created in 11 pigs through an intra-pulmonary injection of contrast-enriched minced muscle. Tumors were ablated under fluoroscopic and 3D-CBCT-guidance using a single microwave antenna. Continuous (CM) and pulsed mode (PM) were used. According to tumor size, 3 different algorithms for both continuous and pulsed mode were used. The ablation zones were measured using post-procedural 3D-CBCT and on pathologic specimens. Results: Two radiologists measured the ablation zones on CBCT and they significantly correlated with macroscopic and microscopic pathological findings: r = 0.75 and 0.74 respectively ( p < 0.0001) (inter-observer correlation r = 0.9). For 1, 2 and 3 cm tumors mimics lesions (TMLs), mean maximal and transverse ablation diameters were 3.6 ± 0.3 × 2.2 ± 0.3 cm; 4.1 ± 0.5 × 2.6 ± 0.3 cm and 4.8 ± 0.3 × 3.2 ± 0.3 cm respectively using CM; And, 3.0 ± 0.2 × 2.1 ± 0.2 cm; 4.0 ± 0.4 × 2.7 ± 0.4 cm and 4.6 ± 0.4 × 3.2 ± 0.4 cm respectively for PM, without any significant difference except for 1 cm TMLs treated by PM ablation which were significantly smaller ( p = 0.009) The sphericity index was 1.6, 1.6, 1.5 and 1.4, 1.5, 1.4 at 1, 2 and 3 cm for CM and PM respectively, p = 0.07, 0.14 and 0.13 for 1, 2 and 3 cm tumors mimics. Conclusion: Microwave ablation for 1–3 cm lung tumors were successfully realized but with a moderate reproducibility rate, using either CM or PM. Immediate post ablation CBCT can accurately evaluate ablation zones.